Perencanaan Implementasi Strategi Creating Shared Value dalam Pengelolaan Limbah Ex - Blasting PT INKA (Persero) - Andhyanerra Irsia Prasasti; Okik Hendriyanto Cahyonugroho (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PT INKA (Persero) is an industry that operates in the field of railway manufacturing. One of the programs consistently carried out by PT INKA (Persero) is Corporate Social Responsibility (CSR). CSR is a commitment by the company to care for sustainable development and provide numerous benefits from social, economic, legal and environmental aspects. The CSR program is oriented towards the Sustainable Development Goals (SDGs). Not Only CSR, but recently several companies or industries have implemented the Creating Shared Value (CSV) strategy, where CSV is a concept of CSR that realizesshared value beneficial to both society and the company. This study focuses on the reuse of ex – blasting waste as paving blocks as strategy for CSV.